Novice Faculty Development at Public Universities in Azerbaijan - Panahli, Laman (ADA University, 2022)
This study aimed to explore the phenomenon of novice faculty development by learning the perception of support from administration and experienced faculty members at Higher education institutions (HEIs); to find out the difficulties that novice faculty members encounter in their early years of being a member of academic staff at HEIs and to contribute to the development of novice faculties at HEIs in Azerbaijan. The issue had never been explored in Azerbaijan. In this regard, it was thought to be necessary to include the study's inadequacies in the literature. This study was significant in terms of adding to the theoretical and practical aspects of novice faculty development, which may be necessary in the Azerbaijani setting. The target population of the study was faculty members and administrative staff members at public HEIs in Azerbaijan. The sample size of the study consisted of 4 novice faculties, 4 experienced faculties, and 4 heads of departments at four public HEIs. Semi-structured interviews were employed to gather the data. According to the findings of the study, HEIs had not identified novice faculty development as a policy mechanism. There was not a formal induction process in place for newly hired faculty members to help them build their professional skills and adjust to their new jobs. Communication, teaching approaches, and differing student mindsets were all major challenges for new faculty members, according to the research. With regard to support from administrative staff and experienced faculty members, it had been revealed that permission for class observation, assistance with class materials were the main types of support that they provide for the novice faculty members.
Keywords: Education, Higher -- Azerbaijan.; Education, Higher -- Azerbaijan -- Challenges.; Professional development.; Mentoring.; Education